Operando swelling measurement of silicon carbon composite based anode in pouch cell: Effect of external pressure, balancing and anode initial porosity. (1st August 2023) - Vidal, Delphine; Genies, Sylvie; De Vito, Eric; Tulodziecki, Michal; Porcher, Willy
Abstract: Silicon lithiation induces a high material expansion, leading to significant swelling and mechanical pressure at the anode and cell levels. In this study, the swelling behaviour of a bilayer pouch cell with high-performance silicon carbon graphite (Si-C/G) anode material was measured, considering the effect of external pressure on the pouch and the cell design parameters such as the balancing and the anode initial porosity. Operando swelling was measured by using an in-house high precision (< 0.1 μm) compression set-up involving simultaneous pressure and thickness recording as well as dynamic pressure regulation system. Results show that a minimum level of pressure is mandatory to obtain a reversible swelling, and that the anode porosity is directly linked to the pressure applied on the cell after particles dynamic rearrangement. The impact on capacity retention is also discussed. Highlights: High precision compression set-up for operando bilayer Li-ion pouch cell swelling Si-based anode cell swelling and capacity retention at constant pressure Investigation of pressure, balancing and anode porosity impacts on anode swelling